Novel lineages of single-stranded DNA phages that coevolved with the symbiotic bacteria Rhizobium - Van Cauwenberghe, Jannick; Santamaría, Rosa I.; Bustos, Patricia; González, Víctor (Frontiers in Microbiology, 2022)
This study describes novel single-stranded DNA phages isolated from common bean agriculture soils by infection of the nitrogen-fixing symbiotic bacteria Rhizobium etli and R. phaseoli. Twenty-nine phages analyzed have 4.3 to 6 kb genomes in size and GC 59-60%. They belong to different clades unrelated to other Microviridae subfamilies. Electron microscopy showed an icosahedral morphology with protrusions at the surface. Three-dimensional models of the major capsid protein (MCP) showed a conserved b-barrel structural “jelly-roll” fold. A variable-length loop in the MCPs distinguished three Rhizobium microvirus groups. Microviridae subfamilies were consistent with viral clusters determined by the protein-sharing network. All viral clusters, except for Bullavirinae, included mostly microviruses identified in metagenomes from distinct ecosystems. Two Rhizobium microvirus clusters, chaparroviruses, and chicoviruses, were included within large viral unknown clusters with microvirus genomes identified in diverse metagenomes. A third Rhizobium microvirus cluster belonged to the subfamily Amoyviridae. Phylogenetic analysis of the MCP confirms the divergence of the Rhizobium microviruses into separate clades. The phylogeny of the bacterial hosts matches the microvirus MCP phylogeny, suggesting a coevolutionary history between the phages and their bacterial host. This study provided essential biological information on cultivated microvirus for understanding the evolution and ecological diversification of the Microviridae family in diverse microbial ecosystems.